Minutes of 6th technical and progress monitoring (TPM) meeting of BRACU new campus (session I) - Brac University (Brac University, 2023)
Minutes of the 6th Technical and Progress Monitoring (TPM) (session I) meeting of BRACU new campus, held on 15th December, 2018.